Level of knowledge about the Argentinean Decriminalization of Abortion in Argentina among students of the Medical School of the Universidad Abierta Interamericana -Sede Rosario inthe year 2023 - Brunela Frade, Melani (2023)
Introduction: Abortion is a medical procedure used to terminate a pregnancy, which is considered a guarantee of the right to a safe and free abortion for women, girls and other persons with gestational capacity to decide about their sexual and reproductive health. Objective: To describe the level of knowledge about the Argentinean Abortion Decriminalization Law among 4th and 5th year students of the Medical School of the Universidad Abierta Interamericana (UAI), Rosario campus, in the year 2023. Materials and methods: Quantitative, descriptive, observational, cross-sectional and retrospective study, carried out at the UAI. The study population consisted of all the students who attended the 4th and 5th year of the 1st four-month period of the Medicine course at the UAI - Rosario campus in the year 2023. The data collection instrument consisted of a 25-question survey, anonymous, voluntary and self-administered, consisting of open and closed questions. Quantitative variables were analyzed through absolute and relative percentage frequencies and summarized through central position measures: mean and dispersion measures: range and standard deviation, while qualitative variables were analyzed through absolute and relative percentage frequencies. Results: A total of 60 medical students were surveyed, 72% of whom were female and 28% male; the mean age was 26.38 ± 6.70 years. The mean age was 26.38 ± 6.70 years. 53% were in their 5th year of studies and 47% in their 4th year. Seventy-seven percent recognized up to what week access to voluntary termination of pregnancy is legal. 92% recognize that they can refuse to perform an abortion, but they must first make a conscientious objection. 98% can differentiate between legalized abortion and decriminalized abortion. 33% do not recognize the maximum time limit for performing an abortion once the will to perform it has been expressed, and 23% do not know that access to abortion is included in the mandatory medical program. Sixty-five percent obtained a high level of knowledge, 33% a medium level and 2% a low level. Conclusion: 65% of the students presented a high level of knowledge about the Argentinean Law on Decriminalization of Abortion, recognizing the necessary guidelines for access to voluntary termination of pregnancy, professional responsibility and the process of comprehensive care for those entitled to termination of pregnancy.